Friction in the Archives: Storytelling in Sixteenth-Century Anabaptism - Lambert, Erin (Renaissance and Reformation / Renaissance et Réforme, 2018)
The writings of martyrs have been at the centre of the history of Reformation-era Anabaptism since the sixteenth century itself, and scholars have long used them as sources of information about a persecuted and typically clandestine community. Based on a rare confluence in the surviving source material—a martyr’s prison letter and a repentant Anabaptist’s request for pardon that provide two different narratives of closely related events—this article reframes martyrological narratives as stories that reveal much about the subjectivity of their authors and the ways in which they shaped the early history of Anabaptism. At the same time, pardon tales can introduce new perspectives into historical narratives that were, over the course of centuries, inscribed as truth through communal practices of singing and reading.